The Role of School Administration Personnel in Building Public Image - Nur, Lulla Alisyah; Maisyaroh, Maisyaroh; Sunandar, Asep (Proceedings Series of Educational Studies, 2024)
This study aims to examine the importance of public image for schools in the era of globalization. A positive school image not only attracts the interest of prospective new students, but also increases community support and strengthens the school's existence in the midst of increasingly fierce competition. This study found that administrative and public relations personnel have a crucial role in shaping the school's image. Administrative personnel are the vanguard of interaction with the community, while public relations functions as a bridge between the school and the community. Both play an important role in building positive relationships and managing public perception of schools. A positive school image can be built through various strategies, such as improving the performance of all school components, establishing cooperation with various parties, improving services, and highlighting achievements. In addition, transparency in school management, as well as creating a conducive physical and learning environment are also important factors. This study concludes that public image is a long-term investment that provides significant benefits for schools.